Hemodynamics and Metabolic Parameters in Normothermic Kidney Preservation Are Linked With Donor Factors, Perfusate Cells, and Cytokines - Weissenbacher, Annemarie; Stone, John P.; Lo Faro, Maria Letizia; Hunter, James P.; Ploeg, Rutger J.; Coussios, Constantin C.; Fildes, James E.; Friend, Peter J. (Frontiers in Medicine, 2022)
Kidney transplantation is the best renal-replacement option for most patients with end-stage renal disease. Normothermic machine preservation (NMP) of the kidney has been studied extensively during the last two decades and implemented in clinical trials. Biomarker research led to success in identifying molecules with diagnostic, predictive and therapeutic properties in chronic kidney disease. However, perfusate biomarkers and potential predictive mechanisms in NMP have not been identified yet. Twelve discarded human kidneys (n=7 DBD, n=5 DCD) underwent NMP for up to 24 hours. Eight were perfused applying urine recirculation (URC), four with replacement of urine (UR) using Ringer’s lactate. The aim of our study was to investigate biomarkers (NGAL, KIM-1, L-FABP), cells and cytokines in the perfusate in context with donor characteristics, perfusate hemodynamics and metabolic parameters. Cold ischemia time did not correlate with any of the markers. Perfusates of DBD kidneys had a significantly lower number of leukocytes after six hours of NMP compared to DCD. Arterial flow, pH, NGAL and L-FABP correlated with donor creatinine and eGFR. Arterial flow was higher in kidneys with lower perfusate lactate. Perfusate TNF-α was higher in kidneys with lower arterial flow. The cytokines IL-1β and GM-CSF decreased during six hours of NMP. Kidneys with more urine output had lower perfusate KIM-1 levels. Median and 6-hour values of lactate, arterial flow, pH, NGAL, KIM-1, and L-FABP correlated with each other indicating a 6-hour period being applicable for kidney viability assessment. The study results demonstrate a comparable cytokine and cell profile in perfusates with URC and UR. In conclusion, clinically available perfusate and hemodynamic parameters correlate well with donor characteristics and measured biomarkers in a discarded human NMP model.